Neutralização de atividades biológicas das peçonhas de serpentes botrópicas pelo extrato aquoso e compostos isolados de Schizolobium parahyba (FABACEAE) - Vale, Luis Henrique Ferreira do (2007)
CHAPTER I - The aqueous extract prepared from Schizolobium parahyba (Sp) leaves, a native plant from Mata Atlantica forest (Brazil), was tested to analyze its ability to inhibit some biological and enzymatic activities induced by Bothrops alternatus and Bothrops moojeni snake venoms. Sp chromatography in Sephadex LH 20 resulted in 3 fractions: F1 (methanolic fraction); F2 (methanol:water fraction, 1:1 v/v); and F3 (aqueous fraction). These fractions were analyzed in terms of its capacity of inhibit the venoms fibrinogenolytic activity. Sp inhibited 100% of lethality, blood incoagulability, hemorrhagic and indirect hemolytic activities for a 1:10 ratio (venom/extract, w/w), and coagulant activity in a 1:5 ratio (venom/extract, w/w) induced by venoms. Venoms fibrinogenolytic activity were also neutralized by Sp in a 1:10 ratio, resulting in total protection of Bβ chain and partial protection for the fibrinogen Aα chain. However, larger ratios of extract/proteins have caused a complete vanishing of all fibrinogen chains possibly caused by Sp precipitation. Interaction tests have demonstrated that for certain extract/proteins ratios Sp precipitates proteins non-specifically suggesting the presence of tannins, which are very likely responsible for the excellent inhibiting effects of the analyzed ophidian activities. Therefore, the fractioning of Sp was carried out aiming at separating these compounds that mask the obtained results. F1 inhibited 100% the venom fibrinogenolytic activity without presenting protein precipitation effect; F2 demonstrated only partial inhibition of these venoms activities. Finally, F3 did not inhibit fibrinogen proteolysis, but presented strong protein precipitating action. We conclude that Sp, together with tannins, also contains other compounds which can present specific toxin inhibition action of snake venoms. CHAPTER II - Do extrato aquoso liofilizado das folhas de Schizolobium parahyba foram isolados quatro compostos ativos, isoquercitrina, miricetina-3-O-glicosídeo, catequina e galocatequina, por cromatografia em Sephadex LH 20 seguido de HPLC semipreparativo em coluna C-18 e identificados por RMN do 1H e 13C. Essa é a primeira vez que estas substâncias são relatadas nesta espécie assim como suas atividades antiofídicas. Após isolamento foram todas testadas frente a atividade hemorrágica e fibrinogenolítica da peçonha de Bothrops alternatus (Bal). Na proporção 1:30 (Peçonha/fração, m/m) a isoquercitrina inibiu parcialmente a atividade hemorrágica; a miricetina-3-O-glicosideo e a catequina não foram capazes de inibir a hemorragia induzida pela Bal e a galocatequina, por sua vez, apresentou uma eficiente neutralização desta atividade da peçonha. Na proporção de 1:100 (Peçonha/fração, m/m) ficou evidenciado o efeito de inibição total da ação fibrinogenolítica da peçonha pela miricetina-3-O-glicosideo; a isoquercitrina não protegeu a proteólise da cadeia Aα do fibrinogênio e inibiu parcialmente a degradação da cadeia Bβ enquanto a catequina e a galocatequina inibiram parcialmente a degradação da cadeia Aα e totalmente a da cadeia Bβ. Dessa forma concluímos que a galocatequina e a miricetina-3-O-glicosideo são excelentes inibidores de toxinas hemorrágicas e fibrinogenolíticas respectivamente. Estudos vindouros como o de modelagem molecular e cristalização de raio-X usando toxinas isoladas e estas substâncias poderão ser de grande importância para o desenho de novas drogas auxiliares do tratamento com soro antiofídico ou para melhor elucidação da relação estruturafunção das toxinas destes venenos.